CT-guided percutaneous skull biopsy using a drill-assisted system: Technical report of two cases. Issue 6 (December 2015) - Wallace, Adam N; Tomasian, Anderanik; Hsi, Andy C; Chang, Randy O; Jennings, Jack W
The OnControl coaxial biopsy system (Vidacare Corporation, Shavano Park, TX) includes an inner diamond-tipped access needle and hollow biopsy needle that engage with a battery-powered hand drill. Herein, we report the use of this novel device to perform two CT-guided percutaneous skull biopsies. Both procedures were performed without complication and facilitated a pathologic diagnosis.